PERANCANGAN SISTEM CUSTOMER RELATIONSHIP MANAGEMENT UNTUK MENINGKATKAN EFISIENSI OPERASIONAL DAN KEPUASAN PELANGGAN - Putrianto, Novenda kartika; Widyastuti, Yuanita Maria; Oktiarso, Teguh (Kurawal - Jurnal Teknologi, Informasi dan Industri, 2024)
This study aims to design and implement an effective Customer Relationship Management (CRM) system for PT XYZ, a company operating in the financial services sector. Through the design phase of the System Development Life Cycle (SDLC), the CRM system is expected to enhance the company’s operational efficiency, particularly in managing customer data, marketing processes, and customer services. The research findings indicate that the developed CRM system successfully meets the identified business needs, such as facilitating customer information management, increasing the effectiveness of marketing activities, and providing faster and more accurate solutions in responding to customer complaints. The implications of this study suggest that a system design tailored to user needs can have a significant positive impact on company performance. Additionally, this research provides practical guidance for other companies in developing CRM systems that align with their specific requirements. However, the study also acknowledges limitations in evaluating the long-term performance of the implemented system. Therefore, future research is recommended to focus on the continuous evaluation of system performance and its impact on customer satisfaction and retention.